2018
DOI: 10.3390/su10030664
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Highly Efficient Atmospheric CO2 Uptake by Artificial Upwelling

Abstract: Artificial upwelling (AU) is considered a potential means of reducing the accumulation of anthropogenic CO 2 . It has been suggested that AU has significant effects on regional carbon sink or source characteristics, and these effects are strongly influenced by certain technical parameters, the applied region, and the season. In this study, we simulated the power needed to raise the level of deep ocean water (DOW) to designated plume trapping depths in order to evaluate the effect of changing the source DOW dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The present situation all over the world shows that the development of a wide variety of artificial downwelling applications, from concept to full-scale sea trial stage, is a difficult, slow, and expensive process. They are possessed with some advantages and limitations and applied in different situations, and their feasibility, survivability, and reliability should be demonstrated [85]. Furthermore, the newness of the concept and the lack of prototype operating experience on which to base designs are a barrier to the implementation of artificial downwelling.…”
Section: Discussionmentioning
confidence: 99%
“…The present situation all over the world shows that the development of a wide variety of artificial downwelling applications, from concept to full-scale sea trial stage, is a difficult, slow, and expensive process. They are possessed with some advantages and limitations and applied in different situations, and their feasibility, survivability, and reliability should be demonstrated [85]. Furthermore, the newness of the concept and the lack of prototype operating experience on which to base designs are a barrier to the implementation of artificial downwelling.…”
Section: Discussionmentioning
confidence: 99%
“…For the artificial upwelling, a control strategy to achieve energy management is also necessary. A carbon sequestration efficiency index is proposed by Pan et al, which is to indicate the effect of artificial upwelling with the power consumption [30]. However, few energy management strategies of artificial upwelling in engineering were found in literatures.…”
Section: Introductionmentioning
confidence: 99%
“…AU is considered as one of the geoengineering techniques that could potentially increase the marine fish productivity and probably accelerate the transfer of CO 2 to the ocean by enhancing the export of organic carbon to the deep ocean by stimulating the rate of photosynthesis of phytoplankton (Ye et al 2013;Hung and Gong 2011;Tsuchiya et al 2017). Simulation models have shown that the highest concentration in the DOW-formed plume could be achieved when optical technical settings of the AU was set according to the regional surface current speed and the vertical density distribution (Fan et al 2015;Pan et al 2015Pan et al , 2018. The enhancement of primary production could be possibly up to 3 times by use of AU (Mizumukai et al 2008;Handå et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The current knowledge on the development of AU systems and their potential environmental effects was reviewed in Pan et al (2016). Briefly, the research on AU over the past few decades has generated a range of devices of different types.…”
Section: Introductionmentioning
confidence: 99%